Improving Students’ Reading Comprehension Skill Using Fable Story Text: A Study at MTs Miftahul Ulum Gondang Wetan Pasuruan - Ulfah Romdoni (JEET, Journal of English Education and Technology, 2025)
This study is to examine: (1) to describe the implementation of using fable story to improve reading comprehension skill at the first grade of Mts Miftahul Ulum Gondang Rejo Gondang Wetan Pasuruan. (2) To know the students’ responses in reading comprehension skill by using fable story at first grade of MTs Miftahul Ulum Gondangrejo Gondangwetan Pasuruan. The researcher is carried out at Mts Miftahul Ulum Gondangrejo Gondangwetan Pasuruan on 23 April 2019, the method used for the research is descriptive qualitative. The data collection technique which is used in this research is observation checklist; it is used to obtain the data of the implementation of the fabled story to improve reading comprehension skill. The result of students responses that are taken from the interview, most of them gave positive reactions in reading comprehension skill by using fable story. And from the score of daily assessment, there are 13 students from 20 students answer the researcher’s question by the excellent answer in the 1st meeting and 15 students from 20 students respond in the 2nd meeting. It's mean that the responses students of MTs Miftahul Ulum Gondangrejo Gondangwetan Pasuruan are interested in the implementation of fable story to be the source of learning reading comprehension skill. Finally, the research can support further researcher. And it is recommended for the English teacher to apply fable story as a source in teaching reading comprehension skill. Moreover, students can comprehend simple text easily